2004
DOI: 10.1046/j.1365-2672.2004.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological characterization and probiotic potential of koko and koko sour water, African spontaneously fermented millet porridge and drink

Abstract: V . L E I A N D M . J A K O B S E N . 2004.Aims: To identify and examine the diversity of predominant lactic acid bacteria (LAB) in koko and koko sour water (KSW) from different Ghanaian production sites with regard to pattern of fermentation (API 50 CHL), genotype, antimicrobial activity, and resistance to low pH and bile salts. Methods and Results: In total 215 LAB were isolated from koko and KSW. The isolates were identified using intergenic transcribed spacers (ITS)-PCR restriction fragment length polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
93
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(115 citation statements)
references
References 59 publications
15
93
1
Order By: Relevance
“…These results corroborate with those of VieiraDalodé et al (2008) in the production of gowè, a sour beverage from Benin, who found a significant increase of LAB count after 4 h of fermentation and during the fermentation step as well as a significantly lower count of yeasts. Our results are also in line with those of Soma (2014) in the production of zoom-koom, Sawadogo-Lingani et al (2007) in the production of dolo and pito, Lei and Jakobsen (2004) in the production of koko and Muyanja et al (2002) in the production of bushera, who found a LAB counts of 10 8 and 10 9 cfu/g during the fermentation process. SawadogoLingani et al (2010) in the traditional malting of sorghum had found a LAB counts which increased from 10 5 to 10 10 cfu/g during the steeping of the sorghum grains.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results corroborate with those of VieiraDalodé et al (2008) in the production of gowè, a sour beverage from Benin, who found a significant increase of LAB count after 4 h of fermentation and during the fermentation step as well as a significantly lower count of yeasts. Our results are also in line with those of Soma (2014) in the production of zoom-koom, Sawadogo-Lingani et al (2007) in the production of dolo and pito, Lei and Jakobsen (2004) in the production of koko and Muyanja et al (2002) in the production of bushera, who found a LAB counts of 10 8 and 10 9 cfu/g during the fermentation process. SawadogoLingani et al (2010) in the traditional malting of sorghum had found a LAB counts which increased from 10 5 to 10 10 cfu/g during the steeping of the sorghum grains.…”
Section: Discussionsupporting
confidence: 92%
“…More ever, many works showed that the organic acids produced during the fermentation of pito in Ghana, tchapalo in Ivory Coast and ben-saalga in Burkina Faso, helped to obtain a better microbial stability of the product (Tou et al, 2006;Dje et al, 2008). Several investigations have shown the involvement of LAB in African traditional fermented cereal-based foods and beverages, including Lactobacillus, Leuconostoc, Lactococcus, Pediococcus and Weissella species (Olasupo et al, 1997;Hayford et al, 1999;Lei and Jakobsen, 2004). The microbiota of many African traditional fermented cereal products have been investigated, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The pearl millet was fermented using the method of Lei and Jacobsen [19]. The pearl millet was sorted to remove extraneous material, thoroughly washed in clean water, soaked soaked in water for 48 h to ferment, the fermented millet was oven-dried to constant moisture, milled and sieved and stored in sealed polythene bag for further processing.…”
Section: Pearl Millet Fermentationmentioning
confidence: 99%
“…Depending on locality, various names may be given to the same product or to products that are basically similar but had slight variations in their production processes [9]. In Kenya, Ghana, South Africia, Sudan, and Ugenda some cereal-based porridges are known as Ikii, Akasa and Koko, Mawe and Ting, Aceda, and Obusera, respectively [10][11][12][13][14][15][16], In Nigeria, Akamu is a traditional lactic acid fermented cereal-based meal, made basically from maize (Zea maize), and other cereals; sorghum or millet [17].…”
Section: Introductionmentioning
confidence: 99%